Pelatihan Aplikasi ENFORCE dalam Mempromosikan Independent Learning bagi Siswa Jurusan Manajemen Perkantoran SMKS Budi Dharma Dumai - Sri Wahyuni; Estika Satriani; Fauzul Etfita; Asnawi Asnawi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service aims to increase the knowledge and capability of SMKS Budi Dharma Dumai students regarding the application of ENFORCE in promoting independent learning. This service method employed training with three stages: first, the pre-activity stage; second, the core activity stage; and third, the evaluation stage. The number of participants in this dedication was nine tenth-grade students majoring in Office Management. The instrument for evaluating this activity used a questionnaire and was analyzed descriptively. The results of this dedication showed that most students favorably responded that ENFORCE was very useful in learning English for office because the material was presented in an exciting and precise manner. From personalization, authenticity, and connectivity, this application is easily accessible, provides original resources, and provides opportunities for self-study. After participating in this training, students stated that they would use this application as an additional learning reference at school and home.